(untitled) (AYUSHDHARA, 2022)
Oral diseases are the commonest Non-Communicable Diseases (NCD). Gum ulcerations, bleeding and bulges associated with pain, burning and itching sensation are common symptoms of Upakusha mentioned in Ayurveda. While Paridara is a later stage, it includes gangrenous gum and bleeding while spitting. These diseases affect teeth as well as the complete body. Maintaining the positive health in healthy individuals and treating the diseased persons are the two main objectives of Ayurveda. In case of oral health, oral hygiene plays a major role in hygiene maintenance well in order to cure a disease. Ayurveda involves Dantapavana, Danta Dhavana, Jihva nirlekhana, Nasya, kavala and Gandusha to maintain oral hygiene and has several medicinal preparations to cure these diseases and scientific validations of the Ayurveda Dental Health practices could justify their role in dental care. In this article, an attempt has been made to spread substantial awareness in society about oral hygiene as well as about the significance of Ayurvedic principles for dental care